The nanotopography of SiO2 particles impacts the selectivity and 3D fold of bound allergens. Issue 48 (2nd December 2021) - Mills-Goodlet, Robert; Johnson, Litty; Hoppe, Isabel J.; Regl, Christof; Geppert, Mark; Schenck, Milena; Huber, Sara; Hauser, Michael; Ferreira, Fátima; Hüsing, Nicola; Huber, Christian G.; Brandstetter, Hans; et al.
Abstract : A detailed description of the changes that occur during the formation of protein corona represents a fundamental question in nanoscience, given that it not only impacts the behaviour of nanoparticles but also affects the bound proteins. Abstract : A detailed description of the changes that occur during the formation of protein corona represents a fundamental question in nanoscience, given that it not only impacts the behaviour of nanoparticles but also affects the bound proteins. Relevant questions include whether proteins selectively bind particles, whether a specific orientation is preferred for binding, and whether particle binding leads to a modulation of their 3D fold. For allergens, it is important to answer these questions given that all these effects can modify the allergenic response of atopic individuals. These potential impacts on the bound allergen are closely related to the specific properties of the involved nanoparticles. One important property influencing the formation of protein corona is the nanotopography of the particles. Herein, we studied the effect of nanoparticle porosity on allergen binding using mesoporous and non-porous SiO2 NPs. We investigated (i) the selectivity of allergen binding from a mixture such as crude pollen extract, (ii) whether allergen binding results in a preferred orientation, (iii) the influence of binding on the conformation of the allergen, and (iv) how the binding affects the allergenic response. Nanotopography was found to play a major role in the formation of protein corona, impacting the physicochemical and biological properties of the NP-bound allergen. The porosity of the surface of the SiO2 nanoparticles resulted in a higher binding capacity with pronounced selectivity for (preferentially) binding the major birch pollen allergen Bet v 1. Furthermore, the binding of Bet v 1 to the mesoporous rather than the non-porous SiO2 nanoparticles influenced the 3D fold of the protein, resulting in at least partial unfolding. Consequently, this conformational change influenced the allergenic response, as observed by mediator release assays employing the sera of patients and immune effector cells. For an in-depth understanding of the bio-nano interactions, the properties of the particles need to be considered not only regarding the identity and morphology of the material, but also their nanotopography, given that porosity may greatly influence the structure, and hence the biological behaviour of the bound proteins. Thus, thorough structural investigations upon the formation of protein corona are important when considering immunological outcomes, as particle binding can influence the allergenic response elicited by the bound allergen.